Perspectives of Bucharest students on automation in contemporary society amid the rise of new artificial intelligence technologies - Beldean, Iulia (Journal of comparative research in anthropology and sociology, 2024)
This study examines the perceptions and approaches of Bucharest students towards emerging Generative Artificial Intelligence (GenAI) technologies and increasing global automation of work. As rapid technological changes affect lifestyles, socialization patterns, routines, and professional futures, industries and governments often prioritize efficiency over individual well-being. The research employs qualitative methods, including one-on-one interviews and a group interview, involving 13 students from diverse academic backgrounds such as STEM, humanities, social sciences, and arts. Data collection spanned six months. Findings reveal a general concern among participants about endangered domains, particularly the arts, due to fears of property theft and plagiarism facilitated by GenAI tools. Notably, the study uncovers a striking contrast between STEM and humanities students regarding future coexistence with these technologies. STEM students tend to perceive a prophetic mission to optimize these technologies, while humanities students focus more on the need for regulation. This research raises important questions about the social construction of reality in interaction with digital technologies and how Generation Z navigates persistent socio-technical acceleration.